Online graphic poster database B -- phase II - Peng, Haiyun. (2013)
As images in modern world have become more important than ever before, the utilization of them also becomes heated topic. Since the quantity of images is so large, different tools had been developed to make use of them. One most famous source of images is the panoramio website. And up to now, there is no tool or program that can make use of the website, yet the resource is so gigantic. So a database that can download and store the images of the website is of great need.